Ch. 249, Subchapter 7-Crimes against Public Health and Safety, §§ 252 & 254 in 1909, Wash. Sess. Laws 965, 966-67 (1909 E. L. Boardman). - (:unkn) unknown (My University, 1909)
Every person who shall make or keep any explosive or combustible substance in any city or village, or carry it through the streets thereof in a quantity, or manner prohibited by law, or by ordinance of such municipality; and every person who, by careless, negligent or unauthorized use or management of any such explosive or combustible substance, shall injure or cause injury to the person or property of another, shall be guilty of a misdemeanor.Every person who shall put up for sale, or who shall deliver to any warehouseman, dock, depot, or common carrier any package, cask or can containing benzine, gasoline, naptha, nitroglycerine, dynamite, powder or other explosive or combustible substance, without having printed thereon in a conspicuous place in large letters the word "Explosive," shall be guilty of a misdemeanor."
Keywords: TRANSFER, MANUFACTURE & STORAGE OF GUNPOWDER